Niat Beli Milenial: Peran Kampanye Pemasaran Dan Media Sosial Serta Bandwagon Effect Produk Fashion Di Tiktok - Pradnyawati, Ni Putu Mareta Manik Indah; Prianthara, Ida Bagus Teddy (Universitas Hamzanwadi, 2024)
This study highlights the influence of social marketing campaigns, social media, and the Bandwagon Effect on millennials' purchase intentions related to fashion products on TikTok. Understanding these dynamics is important in the digital age to devise effective marketing strategies according to the preferences and behaviours of this target market. The purpose of this study is to analyse the influence of social marketing campaigns, social media usage, and Bandwagon Effect on millennial purchase intentions on fashion products on TikTok, with the hope of providing valuable insights for marketers and researchers in the face of the changing digital marketing landscape. The study was conducted in Denpasar City, Bali, with 113 respondents selected using quota sampling. The study model was estimated, validated, and evaluated using Structural Equation Modelling (SEM) with the Partial Least Squares (PLS) method for data analysis. The results showed that social marketing campaigns had no significant effect on millennial purchase intention, while social media usage and Bandwagon Effect had a significant positive relationship with purchase intention. Moderation of the Bandwagon Effect weakens the effect of social marketing campaigns, while moderation of social media usage is not significant